INTERAKSI SOSIAL MUSLIM DAN BUDDHIS (Studi Deskriptif Kuantitatif di Daerah Purbayan, Baki, Sukoharjo Tahun 2016) - Agus Triyono; Mella Oktaviani Anantur (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2016)
AbstractThe main objective of the study is to find out how social interaction among Muslim and Buddhist in Purbayan, Baki, Sukoharjo. Religious as the basis of human behavior has its own way in positioned himself in regulating social relationship society. It is important to maintain the harmony of religious life in the midst of many cases of religious intolerance in Indonesia. The dominant culture and subculture become the main elements in this study. In addition, the uniqueness of oneself or the environment will eventually become the difference that should be given more attention. Effective communication will make it easier to build interaction in diversity ethnicity, religion, and groups that are growing up in the community. Researchers used a variable social interaction andchoose descriptive quantitative analysis with a total of 75 respondents representing Muslim and Buddhist in Purbayan. Collecting data using a questionnaire that is enclosed with the response